﻿A review of the Phyllanthus genus plants: Their phytochemistry, traditional uses, and potential inhibition of xanthine oxidase - Husnunnisa Husnunnisa; Rika Hartati; Rachmat Mauludin; Muhamad Insanu (Pensoft Publishers, 2022)
Hyperuricemia is a risk factor for gout and other cardiovascular diseases. One of the therapies used is Allopurinol. Unfortunately, it has unwanted side effects. These conditions made researchers continue to seek and develop alternative treatments from natural products. One of which is from plants of the Phyllanthus genus. One of their contents was polyphenols, especially flavonoids. It is an alternative treatment for hyperuricemia because of its minimal side effects. The flavonoids in this genus were reported to have xanthine oxidase inhibitory: quercetin, kaempferol, rutin, apigenin, luteolin, myricetin, catechin, epicatechin, and epigallocatechin with IC50 values ​​from 0.44 M to > 100μM. The presence of π-π interactions between planar rings A and C on flavones with phe 1009 and phe 914 and the addition of hydroxyl groups on flavonoid compounds plays a crucial role in inhibiting xanthine oxidase.